Optimisation of Cell Cultures and Cytotoxic Activity of Pereskia Bleo (kunth) dc. Extracts - Sulong, Noor Anilizawatima (2011)
Pereskia bleo (KUNTH) DC is an edible leafy cactus which is known to have anticancer properties among the traditional medicine practitioners. However, up to now there is no scientific evidence to illustrate and confirm such claims. Thus, to discover the potential of P.bleo as a medicinal plants against breast cancer, further research has been conducted. Leaf tissues of P.bleo were used as explants for the induction of callus and cell suspension cultures on different MS media supplemented with 24 different amounts and combinations of NAA and BAP. Callus induced on MS medium supplemented with 2 mg/l NAA and 2 mg/l BAP (Media K) and on MS medium supplemented with 16 mg/l NAA and 2 mg/l BAP (Media W) showed good growth with formation of friable calli. Thus, these cultures were selected for initiation of cell suspension cultures. Elicitation of secondary metabolites was also attempted using pectin and jasmonic acid. Various extracts of P.bleo were prepared and assessed for their cytotoxic activities against two types of cancer cell lines (MCF-7, MDA-MB-231) and against non-tumour 3T3 mouse fibroblast cells. The chloroform crude extracts of the old leaves exhibited the strongest cytotoxic activity against the MCF-7 cell lines with IC50 value of 25.0 μg/ml and slight cytotoxic activity against MDA-MB-231 cells at IC50 64.0 μg/ml. The chloroform extracts of young leaves and the methanol extracts of the old leaves exhibited high cytotoxic activity against the MDA-MB-231 cells with IC50 = 47.0 μg/ml and 43.0 μg/ml, respectively. The non-polar extracts of cell suspension cultures were also found to exhibit cytotoxic activity against the MCF-7 cell lines tested. The petroleum ether extracts of cell suspension in Medium W was found to be most cytotoxic with IC50 <7.5 μg/ml. The IC50 values of chloroform extracts of the cell suspension cultured in the medium W containing jasmonic acid was 27.5 μg/ml and medium W containing pectin was 54.0 μg/ml. The IC50 values for Semi-Purified Compound 1 and Semi-PurifiedCompound 2 against MCF-7 cells were 2.4 μg/ml and 10.4 μg/ml, respectively.Phytochemical analysis of the extracts using the TLC technique revealed that the extracts of the in-vitro cultures showed different TLC profile when compared to the extracts of the field grown plant. Except for the callus and cell suspension cultures, the leaves of P.bleo were found to contain large amount of alkaloids, terpenoids andsaponins. Steroids and triterpenes were found in the non-polar extracts of the leaves andits cell suspension cultures. This study also demonstrated that both the leaves and the invitrocultures of P.bleo (KUNTH) DC. contain potent cytotoxic compounds against the MCF-7 and MDA-MB-231 cell lines. The non-cytotoxic activities of the chloroform extract of the leaves toward the non-tumour 3T3 mouse fibroblasts indicated that the non-polar crude extracts of the leaves exhibited selective mode of inhibition between tumour and non-tumour cells. The result obtained support the reputation of this species as potential anticancer plant.